Pengaruh Implementasi Sistem Coretax terhadap Kepatuhan Wajib Pajak - Pramita Sukma Wardani Mita; Sri Hastari; Hari Wahyuni (FKIP, Universitas Banten Jaya, 2026)
The study investigates the influence of the Coretax system implementation on individual taxpayer compliance by combining the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB) as the underlying theoretical frameworks. A quantitative research design was employed, targeting individual taxpayers registered at the Pratama Tax Office (KPP) of Pasuruan City as the study population. Primary data were gathered through a questionnaire survey and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS version 4.0. The findings reveal that perceived usefulness, perceived ease of use, and subjective norms significantly contribute to improving taxpayer compliance through the utilization of the Coretax system. In addition, each of these factors exerts a positive and statistically significant influence on the adoption and use of the Coretax system. The analysis further demonstrates that greater utilization of the Coretax system is associated with higher level of taxpayer compliance. Overall, the result imply that the effective adoption of digital tax administration systems, such as Coretax, has the potential to strengthen taxpayer compliance by fostering favorable user perceptions and reinforcing social influences that encourage technology acceptance.